Exchange aberrations among 11 chromosomes of human lymphocytes induced by gamma-rays - Cafourková, A; Luká ová, E; Kozubek, S; Kozubek, M; Govorun, R D; Koutná, I; Bártová, E; Skalníková, M; Jirsová, P; Paseková, R; Krasavin, E A (International journal of radiation biology, 2001)
PURPOSE: To detect the frequencies of interchanges among 11 chromosomes in lymphocytes irradiated with gamma-rays and to find out whether these frequencies reflect the proximity of some of these chromosomes within the interphase nucleus. MATERIAL AND METHODS: Exchange aberrations were detected in the first mitosis after irradiation of human lymphocytes with 3 and 5 Gy gamma-rays of 60Co. Two-colour repeated FISH with two differently chemically modified probes in each hybridization was applied. The microscope stage positions of each mitosis were recorded after the first hybridization and used for the automatic scanning of images after all successive experiments. Five images were obtained for each mitosis differing in visualized pairs of chromosomes. Comparing these images, exchanges among 10 chromosomes could be detected. Painting of the p arm of chromosome 21 with the painting probe for chromosome 22 also made it possible to detect exchanges of this chromosome with other chromosomes of the selected group. RESULTS: Frequencies of exchange aberrations induced in chromosomes of the selected group as well as interchanges between many pairs of chromosomes of this group were roughly proportional to the DNA content of chromosomes. Higher frequencies of interchanges than expected according to the model of linear proportionality were found between several chromosomes involved in translocations frequent in different subtypes of leukaemia. CONCLUSIONS: Frequencies of interchanges among 11 chromosomes of human lymphocytes induced by gamma-rays do not indicate as clearly as fast neutrons the non-random arrangement of chromosomes in the cell nucleus. The interaction of a large number of chromosomes in exchange aberrations suggests that the chromatin in the territory of one chromosome is accessible for several other chromosomes.
Keywords: záření gama; Lymphocytes; DNA; lidé; Cells, Cultured; Gamma Rays; lymfocyty; chromozomální aberace; Chromosome Aberrations; kultivované buňky; Humans